2012
DOI: 10.1016/j.jmb.2011.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Glycosyltransferase EryCIII in Complex with its Activating P450 Homologue EryCII

Abstract: In the biosynthesis of the clinically important antibiotic erythromycin D, the glycosyltransferase (GT) EryCIII, in concert with its partner EryCII, attaches a nucleotide-activated sugar to the macrolide scaffold with high specificity. To understand the role of EryCII, we have determined the crystal structure of the EryCIII·EryCII complex at 3.1 Å resolution. The structure reveals a heterotetramer with a distinctive, elongated quaternary organization. The EryCIII subunits form an extensive self-complementary d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 39 publications
(60 reference statements)
1
45
0
4
Order By: Relevance
“…A recent study showed the role of two auxiliary proteins, Srm6 and Srm28, in the activation of two glycosyltransferases, Srm5 and Srm29, respectively, and both are required for the biosynthesis of spiramycin by Streptomyces ambofaciens (42). Activity of the glycosyltransferase EryCIII, which is required for biosynthesis of the antibiotic erythromycin D, is dependent upon an auxiliary protein, EryCII (43). Although the roles of these auxiliary proteins are not clear, it has been proposed that these auxiliary proteins are required to induce conformational changes of the glycosyltransferases, which consequently activate these enzymes (36,42).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed the role of two auxiliary proteins, Srm6 and Srm28, in the activation of two glycosyltransferases, Srm5 and Srm29, respectively, and both are required for the biosynthesis of spiramycin by Streptomyces ambofaciens (42). Activity of the glycosyltransferase EryCIII, which is required for biosynthesis of the antibiotic erythromycin D, is dependent upon an auxiliary protein, EryCII (43). Although the roles of these auxiliary proteins are not clear, it has been proposed that these auxiliary proteins are required to induce conformational changes of the glycosyltransferases, which consequently activate these enzymes (36,42).…”
Section: Discussionmentioning
confidence: 99%
“…141143 EryCII, a homologue of DesVII from the erythromycin biosynthetic pathway in Saccharopolyspora erythraea , was recently confirmed to have the P450-like fold and allosterically activates the GTase EryCIII by forming a homotetramer. 144 By analogy, DesVIII and its homologous non-heme containing P450-like proteins are allosteric activators of macrolide GTases.…”
Section: Functionmentioning
confidence: 99%
“…Apramycin, spectinomycin, and thiostrepton were added to the medium to final concentrations of 100 g/ml, 100 g/ml, and 50 g/ml, respectively. The Escherichia coli strain Turbo was used for cloning, the strain ET12567(pUZ8002) was used to drive the conjugative transfer of nonmethylated DNA from E. coli to the actinomycete recipient, and the strain BL21 Codon Plus RP(pL1SL2) was used for recombinant protein synthesis by applying standard protocols (17)(18)(19)(20)(21).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmid pET28a-ses60310-N-his-Tev was cloned for the heterologous expression of ses60310. Expression was accomplished in E. coli BL21 Codon Plus RP(pL1SL2) (17,20). Optimal production conditions were achieved for cells grown in Luria-Bertani medium at 28°C with shaking at 180 rpm in baffled Erlenmeyer flasks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation